2005
DOI: 10.1103/physrevb.71.085113
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature photoluminescence ofBaTiO3: Joint experimental and theoretical study

Abstract: Strong photoluminescent emission has been measured at room temperature for noncrystalline BaTiO 3 ͑BT͒ perovskite powders. A joint experimental and theoretical study has been carried out to rationalize this phenomenon. From the experimental side, BT powder samples have been synthesized following a soft chemical processing, their crystal structure has been confirmed by x-ray data and the corresponding photoluminescence ͑PL͒ properties have been measured. Only the structurally disordered samples present PL at ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
44
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 107 publications
(50 citation statements)
references
References 31 publications
5
44
0
1
Order By: Relevance
“…This explanation of vector displacement takes into account previous work on the perovskite structure. 23,24 Recently, Lazaro et al 51 reported results of a pre-edge feature of Ti and Ca K-edge XANES in a disordered CaTiO 3 perovskitelike structure. Their findings indicated two types of environments for the calcium, namely, 11-fold and 12-fold calcium coordinations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This explanation of vector displacement takes into account previous work on the perovskite structure. 23,24 Recently, Lazaro et al 51 reported results of a pre-edge feature of Ti and Ca K-edge XANES in a disordered CaTiO 3 perovskitelike structure. Their findings indicated two types of environments for the calcium, namely, 11-fold and 12-fold calcium coordinations.…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24] This emission was attributed to localized levels above the valence band ͑VB͒ and below the conduction band ͑CB͒. Moreover, a charge transfer occurred from the ͓TiO 6 ͔ cluster to the ͓TiO 5 ͔ cluster in the disordered system.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…15 First principle calculations revealed that this disordered structure leads to local polarization and a charge gradient in the structure. 9 We believe that the same mechanism takes place in structurally disordered SZ powders.…”
mentioning
confidence: 94%
“…7 As can be seen, there is no general consensus in the literature to explain why and how radiative decay takes place in perovskitelike structures with a certain degree of disorder. Our group demonstrated that a series of structurally disordered titanates ͑ATiO 3 , where A = Ca, Sr, and Ba͒ displays intense photoluminescence at room temperature when excited by a 488 nm laser excitation line, [8][9][10] and that more intense PL emission is obtained with a certain structural order-disorder in the material.…”
mentioning
confidence: 99%